Pembuatan Pelindung Gadget Berbahan Perca untuk Meningkatkan Kreativitas yang Bernilai Ekonomis Bagi Remaja Panti Asuhan Al-Muthi’in - Mahanani, Chytra; Jerusalem, Moh. Adam; Himmah, Laila Nurul; Elvera, Resi Sepsilia (Abdi Seni, 2023)
In the era of the coronavirus pandemic, people are required to reduce outdoor activities, which affects the economy. One of the efforts to recover economic conditions is by providing skills training and knowledge about creative industries that can be used as capital to increase income. The environment around Al-Muthi'in Orphanage has many resources that can be raised to be developed in the form of creative industries, one of which is the waste of patchwork produced by small fashion industries in Yogyakarta. Creativity and innovation of the students of Al-Muthi'in orphanage need to be developed to capture the opportunities around it. The purpose of training is to increase the creativity of handicrafts of economic value, provide knowledge and insight into the entrepreneurial spirit of the youth of Al-Muthi'in Orphanage so that it can be worth selling, and open home industry opportunities for teenagers Al-Muthi'in Orphanage as an effort to improve the welfare of the family. The target of this activity is the youth of Al-Muthiin Orphanage in Maguwo village, Wonocatur Banguntapan Bantul. The methods used are lectures, demonstrations, training, and practice. The results of the manufacture of gadget-protecting products made of patchwork show that participants understand and are enthusiastic about the manufacture of such products. Through this training, the orphanage youth have the skills to improve the quality of human resources that they can develop to open businesses while creating jobs.